2002
DOI: 10.1029/2001ja000268
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency measurements of HF Doppler velocity in the auroral E region

Abstract: [1] HF measurements in Prince George, British Columbia (Canada), at five radar frequencies between 9.3 and 15.7 MHz are considered to study the Doppler velocity of E region coherent echoes. One event showing a regular variation of velocity with radar frequency, slant range, and azimuth of observations is analyzed in detail. For this event, plasma drifts were in access of 700 m s À1 , but the observed velocities were below 250 m s À1since measurements were performed at large flow angles (L shell angles 45°< f< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 29 publications
8
46
2
Order By: Relevance
“…1. To some extent, this result reminds us of observations of Makarevitch et al (2002a), who reported the absence of the aspect angle attenuation for the Doppler velocity at large L-shell angles φ ∼ =90…”
Section: Discussionmentioning
confidence: 70%
“…1. To some extent, this result reminds us of observations of Makarevitch et al (2002a), who reported the absence of the aspect angle attenuation for the Doppler velocity at large L-shell angles φ ∼ =90…”
Section: Discussionmentioning
confidence: 70%
“…(1) is small the phase velocity is determined by the second term and hence would be representative of the ion drift velocity component alongk and independent of the aspect angle. This argument has been employed by Makarevitch et al (2002) in order to explain an absence of velocity variation with slant range (and hence aspect angle) for certain directions as seen by the Prince George Super-DARN HF radar. The above argument would be valid, however, only for the relatively small range of flow angle near perpendicularity to V d if perfect aspect angle conditions (α=0) are assumed.…”
Section: Discussionmentioning
confidence: 99%
“…More observations casting doubt on the validity of the cosine law have been presented in a series of recent studies by and Uspensky et al (2003) at VHF and by Makarevitch et al (2002Makarevitch et al ( , 2004a and Milan et al (2004) at HF. It has been suggested that the observations could be explained if the ion motion contribution to the phase velocity of E-region irregularities is taken into account as prescribed by generalized formulas of the linear theory in the frame of reference of the neutrals.…”
Section: Introductionmentioning
confidence: 99%
“…These have recently been identified as backscatter from high-aspect angles (the high aspect angle irregularity region (HAIR) echoes), that is from density structures not aligned along the magnetic field, whose Doppler velocity is determined by the ion drift rather than the electron drift Drexler and St.-Maurice 2005). Aspect angle effects have also been found to be important in modifying the Doppler shift characteristics of other echo types (Makarevitch et al 2002.…”
Section: E-region Ionospheric Irregularitiesmentioning
confidence: 99%
“…More recently, SuperDARN observations have challenged this view and it has become clear that the slow background echoes do not represent the background E Â B drift but have u los values that are only *10-40% of v los (Makarevitch et al 2002;Milan et al 2003a;Koustov et al 2005). Understanding that the most ubiquitous echoes are not representative of the electric field prompted a reclassification of the echo-types seen at HF frequencies into five populations i to v, drawing a clear distinction from VHF nomenclature Lester 1999, 2001):…”
Section: E-region Ionospheric Irregularitiesmentioning
confidence: 99%